Lysine and novel hydroxylysine lipids in soil bacteria: amino acid membrane lipid response to temperature and pH in Pseudopedobacter saltans - Moore, Eli K.; Hopmans, Ellen C.; Rijpstra, W. Irene C.; Sanchez Andrea, Irene; Villanueva, Laura; Wienk, Hans; Schoutsen, Frans; Stams, Alfons; Sinninghe Damste, Jaap (Frontiers in Microbiology, 2015)
Microbial decomposition of organic matter is an essential process in the global carbon cycle. The soil bacteria Pseudopedobacter saltans and Flavobacterium johnsoniae are both able to degrade complex organic molecules, but it is not fully known how their membrane structures are adapted to their environmental niche. The membrane lipids of these species were extracted and analyzed using high performance liquid chromatography-electrospray ionization/ion trap/mass spectrometry (HPLC-ESI/IT/MS) and high resolution accurate mass/mass spectrometry (HRAM/MS). Abundant unknown intact polar lipids (IPLs) from P. saltans were isolated and further characterized using amino acid analysis and two dimensional nuclear magnetic resonance (NMR) spectroscopy. Ornithine IPLs (OLs) with variable (hydroxy) fatty acid composition were observed in both bacterial species. Lysine-containing IPLs (LLs) were also detected in both species and were characterized here for the first time using HPLC-MS. Novel LLs containing hydroxy fatty acids and novel hydroxylysine lipids with variable (hydroxy) fatty acid composition were identified in P. saltans. The confirmation of OL and LL formation in F. johnsoniae and P. saltans and the presence of OlsF putative homologues in P. saltans suggest the OlsF gene coding protein is possibly involved in OL and LL biosynthesis in both species, however, potential pathways of OL and LL hydroxylation in P. saltans are still undetermined. Triplicate cultures of P. saltans were grown at three temperature/pH combinations: 30°C/pH 7, 15°C/pH 7 and 15°C/pH 9. The fractional abundance of total amino acid containing IPLs containing hydroxylated fatty acids was significantly higher at higher temperature, and the fractional abundance of lysine-containing IPLs was significantly higher at lower temperature and higher pH. These results suggest that these amino acid-containing IPLs, including the novel hydroxylysine lipids, could be involved in temperature and pH stress response